Differential Immunohistochemical Profiles for Distinguishing Prostate Carcinoma and Urothelial Carcinoma - Woo Jin Oh; Arthur Minwoo Chung; Jee Soon Kim; Ji Heun Han; Sung Hoo Hong; Ji Yeol Lee; Yeong Jin Choi (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background The pathologic distinction between high-grade prostate adenocarcinoma (PAC) involving the urinary bladder and high-grade urothelial carcinoma (UC) infiltrating the prostate can be difficult. However, making this distinction is clinically important because of the different treatment modalities for these two entities. Methods A total of 249 patient cases (PAC, 111 cases; UC, 138 cases) collected between June 1995 and July 2009 at Seoul St. Mary's Hospital were studied. An immunohistochemical evaluation of prostatic markers (prostate-specific antigen [PSA], prostate-specific membrane antigen [PSMA], prostate acid phosphatase [PAP], P501s, NKX3.1, and α-methylacyl coenzyme A racemase [AMACR]) and urothelial markers (CK34βE12, p63, thrombomodulin, S100P, and GATA binding protein 3 [GATA3]) was performed using tissue microarrays from each tumor. Results The sensitivities of prostatic markers in PAC were 100% for PSA, 83.8% for PSMA, 91.9% for PAP, 93.7% for P501s, 88.3% for NKX 3.1, and 66.7% for AMACR. However, the urothelial markers CK34βE12, p63, thrombomodulin, S100P, and GATA3 were also positive in 1.8%, 0%, 0%, 3.6%, and 0% of PAC, respectively. The sensitivities of urothelial markers in UC were 75.4% for CK34βE12, 73.9% for p63, 45.7% for thrombomodulin, 22.5% for S100P, and 84.8% for GATA3. Conversely, the prostatic markers PSA, PSMA, PAP, P501s, NKX3.1, and AMACR were also positive in 9.4%, 0.7%, 18.8%, 0.7%, 0%, and 8.7% of UCs, respectively. Conclusions Prostatic and urothelial markers, including PSA, NKX3.1, p63, thrombomodulin, and GATA3 are very useful for differentiating PAC from UC. The optimal combination of prostatic and urothelial markers could improve the ability to differentiate PAC from UC pathologically.